The Effectiveness Of Cognitive Behavior Therapy Group Counseling With Cognitive Restructuring And Self-Talk Techniques To Reduce Students’ Academic Procrastination - M. Zidni Ilma; Mungin Eddy Wibowo; Anwar Sutoyo (Jurnal Bimbingan Konseling, 2024)
Procrastination is commonly practiced by students who fear failure or have unrealistic expectations to perfectly accomplish tasks. This study attempted to examine the effectiveness of cognitive behavior therapy group counselling with cognitive restructuring and self-talk techniques to reduce the academic procrastination of students at MTs Nurul Huda Demak. It used an experimental method and pretest-posttest control group design by involving 17 students with high tendency of academic procrastination as the subjects. Based on the Wilcoxon test, the intervention previously mentioned could reduce the academic procrastination of the students at MTs Nurul Huda Demak. It is recommended to expand the scope of research subjects by having a control group for conducting the experiment.